2017
DOI: 10.1021/acs.jmedchem.7b01231
|View full text |Cite
|
Sign up to set email alerts
|

Methyl 3-(3-(4-(2,4,4-Trimethylpentan-2-yl)phenoxy)-propanamido)benzoate as a Novel and Dual Malate Dehydrogenase (MDH) 1/2 Inhibitor Targeting Cancer Metabolism

Abstract: Previously, we reported a hypoxia-inducible factor (HIF)-1 inhibitor LW6 containing an (aryloxyacetylamino)benzoic acid moiety inhibits malate dehydrogenase 2 (MDH2) using a chemical biology approach. Structure-activity relationship studies on a series of (aryloxyacetylamino)benzoic acids identified selective MDH1, MDH2, and dual inhibitors, which were used to study the relationship between MDH enzyme activity and HIF-1 inhibition. We hypothesized that dual inhibition of MDH1 and MDH2 might be a powerful appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…This inhibitor blocks both cytoplasmic MDH1 and mitochondrial MDH2 enzymes. It has been shown that intraperitoneal administration of this inhibitor attenuates the development of colon cancer cell xenografts [ 113 ]. Further evaluations of MDH inhibitors, together with the development of specific GOT1, ME1 inhibitors are expected as therapeutic options in pancreatic cancer [ 114 ].…”
Section: Targeting Lipid Metabolism and Therapy Options For Cancermentioning
confidence: 99%
“…This inhibitor blocks both cytoplasmic MDH1 and mitochondrial MDH2 enzymes. It has been shown that intraperitoneal administration of this inhibitor attenuates the development of colon cancer cell xenografts [ 113 ]. Further evaluations of MDH inhibitors, together with the development of specific GOT1, ME1 inhibitors are expected as therapeutic options in pancreatic cancer [ 114 ].…”
Section: Targeting Lipid Metabolism and Therapy Options For Cancermentioning
confidence: 99%
“…Moreover, DEX downregulates the expression of liver fatty acid binding-associated genes and inhibits the expression of the liver mitochondrial matrix acyl-CoA dehydrogenases in mice, which are relevant to free fatty acid (FFA) import and fatty acid oxidation (FAO), respectively [15,16]. Glucose uptake and transport provide the main raw material for cells to synthesize amino acids, nucleotides, lipids, and adenosine triphosphate (ATP) which are necessary for survival and reproduction of cancer cells [17][18][19]. Malignant cells depend on rapid de novo fatty acid synthesis to support their development and growth [20].…”
Section: Introductionmentioning
confidence: 99%
“…(A) Schematic of the DEX treatment schedule. Mice were inoculated subcutaneously with 5 × 10 5 Lewis lung carcinoma (LLC) cells, and on days 7,9,11,13,15,17,19, and 21 post-inoculation, mice were intraperitoneally treated with 0.9% NaCl or various doses of DEX (2 mg/kg, 10 mg/kg, and 50 mg/kg). (B) Representative tumor growth in mice treated with 0.9% NaCl or various doses of DEX (n = 5-6 mice per group).…”
mentioning
confidence: 99%
“…Oxygen consumption was measured using an Oxytherm Clark-type electrode system (Hansatech, Norfolk, UK) as described previously with modifications 32 . HepG2 cells (2 × 10 7 ) were incubated with 2 µM LW1564 for 6 h and harvested, and then the OCR was measured for 5 min at 37°C with a thermos-regulated circulating system.…”
Section: Mitochondrial Respiration Assaymentioning
confidence: 99%